How Artificial Intelligence Used for Legal Referencing? - Baiquni, Muhammaq Iqbal (Knowledge Garden: International Journal of Library Studies, 2023)
The use of artificial intelligence (AI) in the realm of law has become a significant focus in the evolution of legal technology. The optimization of AI in the utilization of legal references aims to enhance efficiency and accuracy in legal research and analysis processes. This research endeavors to examine how AI can be optimized for managing and leveraging available legal references. This study employs an interdisciplinary approach involving computer science, law, and information science. We will evaluate natural language processing and machine learning techniques that can be employed to recognize, categorize, and organize legal references. Furthermore, legal and ethical aspects concerning the use of AI in a legal context, including data privacy and security issues, will be considered. The outcomes of this research are expected to provide practical guidelines for legal professionals, researchers, and technology developers to harness AI optimally in utilizing legal references. By utilizing AI, it is anticipated that legal research processes can become faster, more accurate, and efficient, thereby supporting a fairer and more sustainable legal system in the future.